Aplicação de algoritmos genéticos na otimização de estratégias de manutenção e reabilitação de pavimentos flexíveis - Basso, Luana Caroline Girardi (2021)
Brazilian highways have been the main form of freight and people transportation. However, most part of the highways in the country present some type of deterioration, what makes their users to be the most damaged. Part of this problem can be assigned to the fact that, mostly of the times only the implementation costs are considered when a road is being projected, putting aside the costs that will occur during its lifetime, as the ones of maintenance or rehabilitation, costs that can consume significant part of the investment. In the imminent publication of a new design method, MeDiNa, by the National Department of Transportation Infrastructure, that is under public consultation since 2018, it is believed that a cost analysis of road projects can be of great value for decision makers. Therefore, this paper aimed the development of a tool, to be used together with MeDiNa, to make the life cycle cost analysis of structures dimensioned there and optimization of maintenance strategies of the pavement. Firstly, a module to life cycle cost analysis was developed, using Monte Carlo simulation, for the road implementation costs. A second module was made for the optimization of maintenance and rehabilitation strategies making use of genetic algorithms. After the tool development, one structure was evaluated and validated through results comparison. It was observed that the results obtained in both methodologies had little variability, needing to be emphasized that, in the developed tool, the conservation costs were higher, what resulted in maintenance costs reduced, when confronted to the compared methodology. Users costs represent an important fraction of total costs and the appropriate maintenance of the road contributes to the no increase of this portion, besides reducing the need of more costly interventions.